ҚОРАҚАЛПОҚ БАДИИЙ КИНОСИ (1991-2024 йиллар) - Хужаниязов, У.Е. (SCIENCE and SOCIETY, 2025)
This research paper analyses full-length feature films produced by the «Karakalpakfilm» studio during the years of independence.
Keywords: Independence; art; director; film; studio; short film; actor; comedy; “Karakalpakfilm”